Feeding pineapple waste silage as roughage source improved the nutrient intakes, energy status and growth performances of growing Myanmar local cattle (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The aim of this experiment was to determine the effect of feeding pineapple waste silage (PWS) as the source of roughage replaced in Napier grass silage (NGS) on the nutrient intakes, energy status, and growth performances of growing Myanmar local cattle.  Materials and methods: Eight growing Myanmar local cattle were randomly allocated into two groups, which were adjusted for age, sex, and body weight. Treatments were control (70% NGS + 30% concentrate) and PWS (45% NGS + 25% PWS + 30% concentrate). This experiment lasted for 6 weeks, including adaptation, and feed intake, energy status, and body weight gain were measured.  Results: The higher (p < 0.05) intakes of dry matter, crude protein, non-fiber carbohydrate, neutral detergent fiber and energy, and energy balance were observed in the PSW group than in the control group. Although the initial and final body weights of both groups were not different (p > 0.05), the body weight gain and average daily gain were significantly higher (p < 0.05) in the PSW group than in the control group. Feeding PWS as a roughage source at 25% of diet improved the nutrient intake, energy balance, and body weight gain of growing Myanmar local cattle.  Conclusion: Thus, PWS could be used as the source of roughage replaced in NGS in Myanmar local cattle with the improvement of productive performances.J. Adv. Vet. Anim. Res., 7(3): 436-441, Sep 2020http://doi.org/10.5455/javar.2020.g439